2022
DOI: 10.3390/ijms23041934
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of FGF-2, FGF-18 and Transcription Factor Activity by Perlecan in the Maturational Development of Transitional Rudiment and Growth Plate Cartilages and in the Maintenance of Permanent Cartilage Homeostasis

Abstract: The aim of this study was to highlight the roles of perlecan in the regulation of the development of the rudiment developmental cartilages and growth plate cartilages, and also to show how perlecan maintains permanent articular cartilage homeostasis. Cartilage rudiments are transient developmental templates containing chondroprogenitor cells that undergo proliferation, matrix deposition, and hypertrophic differentiation. Growth plate cartilage also undergoes similar changes leading to endochondral bone formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 170 publications
(242 reference statements)
0
23
0
Order By: Relevance
“…While the HS chains of perlecan play indispensable roles in embryogenesis and skeletogenesis, they can also inhibit adult tissue repair processes. Degradation of HS in situ improves wound healing and tissue repair through the re-mobilization of previously sequestered FGF-2, which was unavailable to promote tissue repair, as the results demonstrated that heparanase releases FGF-2 in tissues in an activated form, which promotes wound healing [45,103].…”
Section: Universal Perlecan Changes In Oamentioning
confidence: 98%
See 2 more Smart Citations
“…While the HS chains of perlecan play indispensable roles in embryogenesis and skeletogenesis, they can also inhibit adult tissue repair processes. Degradation of HS in situ improves wound healing and tissue repair through the re-mobilization of previously sequestered FGF-2, which was unavailable to promote tissue repair, as the results demonstrated that heparanase releases FGF-2 in tissues in an activated form, which promotes wound healing [45,103].…”
Section: Universal Perlecan Changes In Oamentioning
confidence: 98%
“…Heparanase in OA cartilage induces catabolic responses [103] but also downregulates anabolic genes. Reduced HS levels, reduced HS sulfation, and alterations in HS fine structure were observed in OA cartilage, which had decreased degenerative OA histopathology scores [43].…”
Section: Universal Perlecan Changes In Oamentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt proteins are secreted, lipid-modified glycoproteins which form morphogen gradients that direct cellular behaviour to produce these effects [ 28 ]. Wnt proteins however are hydrophobic and poorly soluble in aqueous media, heparan sulfate proteoglycans (HS-PGs) are necessary for the proper activity of Wnt proteins maintaining their solubility and these also transport Wnt proteins aiding in the formation of Wnt gradients in tissues which drive developmental processes [ 29 ]. Wnt binds to the LDLR domain II of perlecan and this acts as a Wnt delivery vehicle in tissue development [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wnt proteins however are hydrophobic and poorly soluble in aqueous media, heparan sulfate proteoglycans (HS-PGs) are necessary for the proper activity of Wnt proteins maintaining their solubility and these also transport Wnt proteins aiding in the formation of Wnt gradients in tissues which drive developmental processes [ 29 ]. Wnt binds to the LDLR domain II of perlecan and this acts as a Wnt delivery vehicle in tissue development [ 29 , 30 ]. HS-PGs are also pericellular and basement membrane ECM components and have roles in synapse stabilization in neural tissues important in synaptic plasticity and neuron interactivity within neural networks of the central and peripheral nervous systems (CNS & PNS, respectively) [ 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%